Effects of Li+ transport and Li+ immobilization on Li+/Mg2+ competition in cells: implications for bipolar disorder - Layden, Brian T. (2003)
Li+/Mg2+ competition has been implicated in the therapeutic action of Li+ treatment in bipolar illness. We hypothesized that this competition depended on cell-specific properties. To test this hypothesis, we determined the degree of Li+ transport, immobilization, and Li+/Mg2+ competition in lymphoblastomas, neuroblastomas, and erythrocytes. During a 50 mmol/L Li+-loading incubation, Li+ accumulation at 30 min (mmoles Li+/L cells) was the greatest in lymphoblastomas (11.1±0.3), followed by neuroblastomas (9.3±0.5), and then erythrocytes (4.0±0.5). Li+ binding affinities to the plasma membrane in all three cell types were of the same order of magnitude; however, Li+ immobilization in intact cells was greatest in neuroblastomas and least in erythrocytes. When cells were loaded for 30 min in a 50 mmol/L Li+-containing medium, the percentage increase in free intracellular [Mg2+] in neuroblastoma and lymphoblastoma cells (~55 and ~52%, respectively) was similar, but erythrocytes did not exhibit any substantial increase (~6%). With the intracellular [Li+] at 15 mmol/L, the free intracellular [Mg2+] increased by the greatest amount in neuroblastomas (~158%), followed by lymphoblastomas (~75%), and then erythrocytes (~50%). We conclude that Li+ immobilization and transport are related to free intracellular [Mg2+] and to the extent of Li+/Mg2+ competition in a cell-specific manner.